Kebijaksanaan Pembangunan Perkotaan Di Indonesia: Aspek-Aspek Penting Untuk Operasionalnya - Budhy Tjahjati S Soegijoko (Journal of Regional and City Planning, 1995)
In the future, there will be a shift in the pattern of managing urban development activities. Conventional method that is oriented more on the physical aspect relied more on the government ideas and initiative, referred more on the historical development trend and more "inward looking" toward the country, will not be appropriate to be used as the basis of urban development management in the future. To face all those challenges, a new breakthrough in managing urban development is needed.